ETHICS IN LOCAL INFORMATION SERVICES BROADCASTED IN TRANS-REGIONAL RADIO STATIONS IN POLAND - Jedruchow, Tomasz Dawid (European Scientific Journal, ESJ, 2014)
For many years, the rules of ethical behavior in the media is one of the most important scientific issues. The increasing specialization of the media makes it in many cases very difficult to maintain the objectivity of the information. It is especially difficult when you are dealing with trans-regional media, which can not only broadcast throughout the country but also locally. The specific structure of the program makes the keeping of the rules of journalistic ethics requires many efforts. Article informs us about the specifics of local news in the trans-regional radio stations. Due to their nature, it's very hard to keep the rules of journalistic ethics. Although it is not impossible. The text presents not only the difficulties that journalists of trans-regional radio stations have to face but also possibilities of avoiding staying in conflict with the principles of journalistic ethics. Method that was used in text is ethnographic case study. It was examined an example of trans-regional radio station operating on the basis of trans-regional concessions. Ethnographic case study method was possible to use due to the fact that the author of the publication was an employee the audited station, so that he could to learn the rules of its functioning from the inside.